The Role of Kyai's Charismatic Leadership in Mitigating Religious Intolerance and Radicalism in Pesantren - Ali Nasith (International Journal of Social Science and Religion (IJSSR), 2024)
This research discusses the critical role of kyai's charismatic leadership in mitigating religious intolerance and radicalism in pesantren. Kyai, as the primary leader in pesantren, has a significant influence in shaping the attitudes and thoughts of the santri. This research was conducted based on a field analysis study, followed by literature research incorporating various scientific arguments and information from relevant literature sources. This research was implemented at Pondok Pesantren Sabilurrosyad Gasek as a sample object, involving kyai, santri, and the surrounding community. Through his charisma and authority, the kyai can effectively convey the values of religious moderation to the santri. The approach taken by the kyai, which emphasizes the values of deliberation, balance, and tolerance, helps the santri understand religious teachings in a balanced manner and avoid radical attitudes. Islamic boarding schools also play a role in instilling religious moderation values through a well-structured religious education curriculum. Thus, the charismatic leadership of kyai is at the forefront of reducing religious intolerance and radicalism in pesantren, forming a generation of santri who understand religious teachings comprehensively and moderately, and contributing to creating an inclusive and peaceful society.